Consideration of sex/gender in publications of quantitative health-related research: Development and application of an assessment matrix - Horstmann, Sophie; Hartig, Christina; Kraus, Ute; Palm, Kerstin; Jacke, Katharina; Dandolo, Lisa; Schneider, Alexandra; Bolte, Gabriele (Frontiers in Public Health, 2023)
During the last years the need to integrate sex and gender in health-related research for better and fairer science became increasingly apparent. Various guidelines and checklists were developed to encourage and support researchers in considering the entangled dimensions of sex/gender in their research. However, a tool for the assessment of sex/gender consideration and its visualization is still missing. We aim to fill this gap by introducing an assessment matrix that can be used as a flexible instrument for comprehensively evaluating the sex/gender consideration in quantitative health-related research. The matrix was developed through an iterative and open process based on the interdisciplinary expertise represented in our research team and currently published guidelines. The final matrix consists of 14 different items covering the whole research process and the publication of results. Additionally, we introduced a method to graphically display this evaluation. By developing the matrix, we aim to provide users with a tool to systematically compare sex/gender consideration qualitatively between different publications and even different fields of study. This way, the assessment matrix represents a tool to identify research gaps and a basis for future research. In the long term, the implementation of this tool to evaluate the consideration of sex/gender should contribute to a more sex/gender equitable health-related research.